2008
DOI: 10.1083/jcb.200805146
|View full text |Cite
|
Sign up to set email alerts
|

UBF levels determine the number of active ribosomal RNA genes in mammals

Abstract: In mammals, the mechanisms regulating the number of active copies of the ∼200 ribosomal RNA (rRNA) genes transcribed by RNA polymerase I are unclear. We demonstrate that depletion of the transcription factor upstream binding factor (UBF) leads to the stable and reversible methylation-independent silencing of rRNA genes by promoting histone H1–induced assembly of transcriptionally inactive chromatin. Chromatin remodeling is abrogated by the mutation of an extracellular signal-regulated kinase site within the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
241
2
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(271 citation statements)
references
References 51 publications
19
241
2
5
Order By: Relevance
“…Depletion of UBF was shown to silence rDNA and its total ablation is likely incompatible with life. 17,18 In agreement, UBTF is highly intolerant to both deleterious and missense variants; in the ExAC cohort, the number of UBTF variants markedly deviate from the expected by its length (Z ¼ 5.61) with expected/observed number of missense variants 295/98 and of loss-of-function (LOF) variants 36/0.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Depletion of UBF was shown to silence rDNA and its total ablation is likely incompatible with life. 17,18 In agreement, UBTF is highly intolerant to both deleterious and missense variants; in the ExAC cohort, the number of UBTF variants markedly deviate from the expected by its length (Z ¼ 5.61) with expected/observed number of missense variants 295/98 and of loss-of-function (LOF) variants 36/0.…”
mentioning
confidence: 76%
“…26 Finally, UBF is an important regulator of chromatin structure at the rDNA locus; it was shown to outcompete linker Histone H1 resulting in decondensation of rDNA chromatin. 17 Changes in chromatin status at the rDNA locus, coupled with nucleolar alterations, have been previously reported in Huntington disease [MIM 143100] 16 and were regulated by UBF post-translational modification by acetylation at Lys-352 and methylation at Lys-232. 16,27 The abnormally increased nucleolar size and reduced number of nucleoli per cell which was observed in the cells of the affected individual, suggest that the mutant hyperactive UBF causes an alteration in rDNA chromatin structure.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…It has been reported that UBF interacts with CTCF and that CTCF binding enhances the recruitment of UBF to the rDNA locus (47). Nucleolar UBF, in turn, ensures that rDNA repeats remain accessible to RNA polymerase I (47).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that UBF interacts with CTCF and that CTCF binding enhances the recruitment of UBF to the rDNA locus (47). Nucleolar UBF, in turn, ensures that rDNA repeats remain accessible to RNA polymerase I (47). Our experiments showed that the binding of UBF onto the rDNA repeat increases significantly after CTCF overexpression and that down-regulation of SMC2 further enhances this effect, which suggests that CTCF, as a mediator, regulates RNA polymerase I-mediated rRNA gene transcription.…”
Section: Discussionmentioning
confidence: 99%